A Modification to the Goldstein RadarInterferogram Filter - Baran, Ireneusz; Stewart, Michael; Kampes, B.; Perski, Z.; Lilly, Peter (2003)
We present a modification to the adaptive Goldstein radar interferogram filter which improves the quality of interferometry products. The proposed approach makes the Goldstein filter parameter alpha dependent on coherence, suchthat incoherent areas are filtered more than coherent areas. This modification minimizes loss of signal while still reducing the level of noise.